2017
DOI: 10.1136/bmjsem-2016-000143
|View full text |Cite
|
Sign up to set email alerts
|

Update on the effects of physical activity on insulin sensitivity in humans

Abstract: Purpose and methodsThis review presents established knowledge on the effects of physical activity (PA) on whole-body insulin sensitivity (SI) and summarises the findings of recent (2013–2016) studies.Discussion and conclusionsRecent studies provide further evidence to support the notion that regular PA reduces the risk of insulin resistance, metabolic syndrome and type 2 diabetes, and SI improves when individuals comply with exercise and/or PA guidelines. Many studies indicate a dose response, with higher ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
288
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(340 citation statements)
references
References 101 publications
19
288
0
8
Order By: Relevance
“…The mechanisms underlying the association between physical inactivity and cognitive impairment remain to be elucidated. Insulin resistance (IR) is closely associated with inactivity and obesity, and PA improves IR . IR is also associated with cognitive impairment at least partly because insulin‐like signaling in the brain is crucial to promote neuronal survival and longevity …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying the association between physical inactivity and cognitive impairment remain to be elucidated. Insulin resistance (IR) is closely associated with inactivity and obesity, and PA improves IR . IR is also associated with cognitive impairment at least partly because insulin‐like signaling in the brain is crucial to promote neuronal survival and longevity …”
Section: Introductionmentioning
confidence: 99%
“…Insulin resistance (IR) is closely associated with inactivity and obesity, and PA improves IR. 10 IR is also associated with cognitive impairment 11 at least partly because insulin-like signaling in the brain is crucial to promote neuronal survival and longevity. 12 The association between cognitive impairment and inactivity might occur through the mechanism of IR, but this has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors related to lifestyle, including regular physical exercise and diet/weight loss, are known to positively affect IS [51,52]. TLC, which improve IS (i.e.…”
Section: Blood Glucose Concentrations and Their Time-integrated Valuementioning
confidence: 99%
“…A study conducted by Mason et al () showed that weight loss improved the insulin resistance of inactive and overweight/obese postmenopausal women. Weight loss, either by dietary control or performing physical activities, may facilitate better insulin response in obese individuals (Bird & Hawley, ). In line with the aforementioned findings, it can be postulated that it is an ideal approach to improve insulin sensitivity in obese individuals.…”
Section: Introductionmentioning
confidence: 99%